The effect of the educational props strategy on the achievement and lateral thinking of second grade female students (Journal of the College of Basic Education, 2022)
Thepaper aims to find out the effectiveness of educational props strategy in the collection and lateral thinking for the students of the second average in mathematics, formed the research sample of 60 female students were divided evenly into two groups, the first experimental studied strategy props educational and a control group studied in the usual way and has parity process of parity between them in several variables, prepared to search tools first achievement-type multiple-choice test: the number of paragraphs (30) items, and test lateral thinking (40) items, and manipulate search results procedures statistically used appropriate statistical methods, and results showed after analysis, no statistically significant differences at level (0.05) between the experimental group and the control group in the achievement test and test lateral thinking and in favor of the experimental group.